Atributos que os anunciantes buscam em um veículo de comunicação para se relacionar com a geração Y - Silva, Cátia Almeida da (Universidade do Vale do Rio dos Sinos, 2013)
From the understanding of the main characteristics and behaviors that guide the relationship of the Generation Y with the brands and the media, this research aimed to identify from the media departments of major advertising agencies in Porto Alegre, how Atlântida Radio is working with this target audience. In order to achieve the objective, a bibliographic review was done and later a semi-structured interview with professionals of the field was taken as a data collection technique. Among the main authors the highlighted ones were Tapscott (2010) Calliari (2012). Yarrow e O'Donnell (2009), Telles (2009), Jenkins (2009) e os resultados da pesquisa da Edelman e StrategyOne, 8095 (2008) e Dossiê MTV 5 (2010). Interviews were conducted with six professionals of the field of media in Porto Alegre. From their answers, we obtained, through the analysis, the main points of work that this audience wishes to establish with brands, changing and demanding more attention to the objectives of the field of media and consequently of the means of communication.
Keywords: Rádio Atlântida FM; Geração Y; Mídia; FM Atlântida Radio; Generation Y; Media